Tindak Tutur Ekspresif dalam Podcast Close The Door Deddy Corbuzier Pada Episode â€œCoba Ibu Jawab JHT Gimanaâ€ - Milli Ana (Institut Agama Islam Negeri Curup, 2022)
In an interaction, speakers and speech partners need good communication to express information that fits the context. Expressive speech acts are the way speakers express their intentions, thoughts, and feelings. The purpose of this study is to describe the function, and meaning of expressive speech acts contained in the Deddy Corbuzier podcast episode